La tensione telica, in equilibrio tra le forme: Crónica de una muerte anunciada e l’ambizione di un ingranaggio perfetto - Abignente, Elisabetta (Status Quaestionis, 2013)
Short story, detective novel, reportage, tragedy: Crónica de una muerte anunciada (1981) cannot be ascribed to any specific genre. Nonetheless, Gabriel García Márquez’s work greatly depends on the ways in which these specific genres face the problem of coincidences while labeling them in a variety of ways, e.g. contingency, chance, fate, destiny, necessity, even guilt. Making reference to the work that García Márquez considers his «perfect story», this article aims to explore how the debate on coincidences inevitably intersects the problem of literary forms.